Anti-inflammatory agents of the carbamoylmethyl ester class: synthesis, characterization, and pharmacological evaluation - Sadek B; Hamruoni AM; Adem A (Dove Medical Press, 2013)
Bassem Sadek,1 Amar Mansuor Hamruoni,2 Abdu Adem1 1Department of Pharmacology and Therapeutics, College of Medicine and Health Sciences, United Arab Emirates University, 2Department of Pharmaceutical Sciences, College of Pharmacy, Al Ain University of Science and Technology, Al-Ain, United Arab Emirates Abstract: In this study, target compounds 5–12 were synthesized via acid amine coupling of ibuprofen and naproxen with methyl ester derivatives of amino acids, namely, l-proline, sarcosine, l-tyrosine, and l-glutamic acid. When tested for anti-inflammatory activity using the acute carrageenan-induced hind paw method in rats, compounds 5–12 showed significantly greater anti-inflammatory activity, in the range of 40.64%–87.82%, compared with a placebo control group (P < 0.001). Among the newly synthesized compounds 5–12, naproxen derivatives 9–12 with anti-inflammatory activity ranging between 66.99% and 87.82% showed significantly higher (P < 0.05) potency than ibuprofen derivatives 5–8 with inhibition in the range of 22.03%–52.91% and control groups of ibuprofen (76.34%) or naproxen (75.59%, P < 0.05). Moreover, derivatives 9–12 derived from naproxen, in particular compounds 9 and 10 which achieved 83.91% and 87.82% inhibition of inflammation, respectively, showed significantly (P < 0.05) higher potency than naproxen derivatives 11 and 12. Notably, among naproxen derivatives 9–12, the gastric ulcerogenicity for 9 (ulcer index 11.73) and 10 (ulcer index 12.30) was found to be significantly lower (P < 0.05) than that of the active ibuprofen and naproxen control groups with ulcer indices of 22.87 and 24.13, respectively. On the other hand, naproxen derivatives 9–11 showed significant inhibition (P < 0.05) of prostaglandin E2 synthesis when compared with the active control group receiving indomethacin, suggesting a correlation between the observed low ulcerogenicity and effect on prostaglandin E2 synthesis for compounds 9 and 10. However, significant inhibition of prostaglandin E2 observed for naproxen derivative 11 (107.51) did not correlate with its observed ulcer index (16.84). Our overall findings for carbamoylmethyl ester derivatives named 5–12 clearly suggest that the compounds showing potent antiinflammatory effect. Keywords: carbamoylmethyl ester, anti-inflammatory, prostaglandin E2, inhibitory properties